PENGARUH HARGA, KUALITAS LAYANAN DAN PROGRAM PROMOSI TERHADAP KEPUTUSAN PEMBELIAN BERKELANJUTAN - Uswatun Chasanah; Muhammad Fauzan (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
This study examined the effect of price, service quality and promotion on sustainable purchasing decisions. The sample used was 60 respondents with the criteria of respondents who used Mamochi products in Yogyakarta. The data was collected using non probability sampling method with purposive sampling technique. The results of the validity test with the Pearson correlation criteriagreather than 0.254 (r table), showed that all indicators were valid, as well as the reliability test with Cronbach alphagreather than 0.6. The results of the mediation test show that consumer satisfaction mediates the effect of price on repurchase decisions, while the quality of service and promotion programs have an effect on repurchase decisions not mediated by customer satisfaction. As for partial testing of price variables, service quality has an effect on satisfaction, while promotion has no effect. Likewise, the variables of price, promotion and customer satisfaction have an effect on repurchase decisions, while service quality has no effect on re-purchase decisions. For the simultaneous test results, price variables, service quality and promotion have an effect on customer satisfaction.